2013
DOI: 10.1007/s00405-013-2539-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-contamination and cross-infection risk of otoscope heads

Abstract: Adequate disinfection level of the medical equipments should be maintained to prevent cross-contamination between patients. Otoscope specula are usually cleaned and disinfected appropriately after each use by disinfectant solutions. However, since otoscope heads are electrical instruments with irregular inner surface they may still harbor pathogenic microorganisms. According to manufacturers' instructions, otoscope heads can be cleaned externally with a damp cloth and they can be disinfected with aldehydes, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…[21][22][23] OCs are instruments with irregular inner surface that may harbor pathogenic microorganisms. 5 According to manufacturer's instructions, OCs can be cleaned externally with a damp cloth and they can be disinfected with aldehydes, surfactants, and alchohols. 5,24,25 In human medicine, a previous work evaluated 53 OCs by sampling for microbiological evaluation and 22 were found to be contaminated with bacteria and/or fungi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[21][22][23] OCs are instruments with irregular inner surface that may harbor pathogenic microorganisms. 5 According to manufacturer's instructions, OCs can be cleaned externally with a damp cloth and they can be disinfected with aldehydes, surfactants, and alchohols. 5,24,25 In human medicine, a previous work evaluated 53 OCs by sampling for microbiological evaluation and 22 were found to be contaminated with bacteria and/or fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Since OCs are reusable equipment, they can be mechanical carriers of cross-contamination and cross infection between patients. 1 OCs are in contact with the integument of the ear canal and thus may be easily become contaminated with a variety of microorganisms. 2 The human medical literature supports the concern for potential iatrogenic inoculation of bacteria into a susceptible ear canal, if cleaning and disinfection are unappropriated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms on a fomite, which may remain viable for days or months, could be transmitted among patients and hospital personnel [3]. Several studies have demonstrated the bacterial contamination of non-critical medical devices (NCMDs), such as otoscopes, white coats, pens, goggles, and other surfaces [3], [4], [5], [6], [7], [8]. In China, the flashlight is a basic NCMD for healthcare workers.…”
Section: Introductionmentioning
confidence: 99%